Dual-Band Notch Filter Based on Twist Split Ring Resonators - Haibin Sun; Cai Feng; Yongjun Huang; Ruiming Wen; Jian Li; Weijian Chen; Guangjun Wen (International Journal of Antennas and Propagation)
A novel dual-band rectangular waveguide notch filter is experimentally investigated in this paper. Such filter is realized by integrating two pairs of split ring resonators (SRRs) printed on the two sides of a dielectric slab with twist angles and separated as a distance in the center of the rectangular waveguide. Due to the coupling effects between the twist SRRs and between the original SRRs and their mirror images generated by the metallic walls perpendicular to the E-field direction, it can flexibly contribute two disjunct resonance states and result in the dual-band notch properties. Furthermore, the two resonance frequencies can be controlled by changing the twist angles, resulting in the shifts of notch frequency bands.